IMF Staff papers : Volume 26 No. 4. (IMF Staff Papers; IMF Staff Papers ;, 1979)
This paper reports the unfinished business of the 1974 Report to the Board of Governors on Reform of the International Monetary System on the question of the Special Drawing Right (SDR) as a basket of currencies. The SDR basket was revised after an initial period of four years and is subject to further revision at intervals of five years on the basis of an announced formula. Although the standard basket SDR has the properties that permit it to become a market asset, this is not the case for an SDR valued on the basis of any of the alternative methods considered in the C-20. The basic reason is that these other SDRs are not combinations of existing currencies but assets that have no counterpart in the market. In the adjustable basket, the divergence between currencies in the basket and currencies in the market occurs not only at the lower end of the range but at the upper end as well.